Heterotypic neutrophil-in-tumor structure: A novel pathological feature first discovered in the tissues of OPSCC - Fan, Jie; Li, Peng; Fang, Qigen; Yang, Yang; Zhang, He; Du, Wei; Liu, Shanting; Luo, Ruihua (Frontiers in Oncology, 2022)
Objective To reveal a novel pathological feature: heterotypic neutrophil-in-tumor structure (hNiT) first discovered in patients with oropharyngeal squamous cell carcinoma (OPSCC), to analyze the prognostic role of hNiT in OPSCC patients and to explore the role of p16 in the formation of hNiT structures. Methods Clinically, 197 patients were enrolled. Clinicopathological information was extracted and analyzed. All pathologic sections made from primary tumors were re-evaluated by immunohistochemistry and immunostaining. In vitro, we cocultured OPSCC cell line SCC-15 with neutrophils to form hNiT structures, which were then subject to fluorescence staining. By RNAi and overexpression techniques, we investigated the role of CDKN2A in the formation of hNiTs. We validated the two techniques by qPCR and Western Blot. Results The hNiT as a novel pathological feature was first discovered in the tissues of OPSCC. The FNiT was significantly associated with tumor stage, disease stage, p16 and tumor grade. A total of 119 patients died of the disease, and the 5-year disease-specific survival (DSS) rate was 36%. The median survival time was 52.6 months. In patients with an FNiT<0.5%, the 5-year DSS rate was 40%; in patients with an FNiT>=0.5%, the 5-year DSS was 28%, and the difference was significant (p=0.001). Cox model analysis showed that FNiT along with disease stage, p16 and tumor grade was an independent prognostic factor for DSS. Immunostaining results of p16 expression showed hNiT formation was negatively correlated to p16 in OPSCC as well as in the hNiT formation assays in vitro indicated by fluorescent staining. Function assays of CDKN2A implied that reduce CDKN2A promoted the formation of hNiT while elevated CDKN2A impeded the hNiT formation. Conclusion The hNiT as a novel pathological feature is associated with the adverse prognosis of OPSCC patients with p16 inhibiting the formation of hNiT structures.